Screening and molecular characterization of cellulase producing bacteria from Fruit wastes - VINOTHA .T,; UMA MAHESWARI .N, (International Journal of Pharma and Bio Sciences, 2018)
Cellulose is one of the most abundant biomass on earth. Cellulases are among the most important industrial hydrolytic enzymes and are synthesized by microorganisms during their growth on cellulosic materials. The present study was aimed to isolate and screen the potential cellulolytic bacteria from fruit wastes. A total of four bacterial cultures were isolated from the different cellulosic fruit waste materials, (Jackfruit peel, custard apple shell, Sweet lime shell and Pineapple peel) based on morphology and biochemical characterization and screened for cellulose production using a submerged fermentation. Optimization was carried out for the maximum cellulose yielding substrate. Among all isolated strains, the highest cellulolytic bacterial strain, based on maximum enzyme activity is named as TPL-2. This bacterium was identified as Enterobacterclocea based on the results of the 16S ribosomal DNA analysis, morphological characteristics, and biochemical properties. Enterobacter clocea is the highest producer of cellulose (8.70 IU/ml/min), followed by Cellulomonas sp (7.410 IU/ml/min), Citrobactersp (5.357 IU/ml/min) and Streptococcus sp(3.334 IU/ml/min) respectively.Under these optimized fermentation conditions, the maximum Cellulase activity at 8.70 IU/ml the optimum pH(7) and temperature (40ºC) optimization progress was also performed. Our study clearly indicates that fruit waste is an attractive source for the study of novel cellulolytic bacteria for cellulose production.